Durable and Flexible PET‐Based Bending Sensor Obtained by Immobilizing Carbon Nanotubes via Surface Micro‐Dissolution for Body Motion Monitoring. Issue 1 (16th November 2021) - Wu, Ziqin; Yang, Fa; Yang, Jinlong; Yang, Pu; Zhang, Xiaolei; Zhang, Tonghua; Lu, Ming
Abstract: Textile‐based conductive materials that can retain their electrical conductivity during bending have been extensively investigated and applied in flexible electronics and wearable sensors; however, the fastness of the conductive components in textiles requires improvements. Herein, a facile and effective surface micro‐dissolution method is developed to prepare carbon nanotubes (CNTs)‐coated PET fabric by embedding CNTs onto the surface of PET fabric. The micro‐dissolved layer of the macromolecule served as a physical adhesion agent to firmly immobilize the CNTs on the PET fabric. The CNTs‐coated PET fabric exhibited an electrical conductivity of 98.1 Ω □ −1, durability during washing (over 30 cycles) and abrasion cycles (over 500 cycles), and remained conductive in harsh environments (high temperature, high humidity, water, corrosive liquids, organic solvents). The sensor (CCPFS) assembled by the CNTs‐coated PET fabric is flexible (over 500 bending cycles), highly sensitive (1.48 deg −1 ), responsive (100 ms), and showed a relaxation time of 200 ms. The CCPFS is used to monitor movements in human fingers, wrist, elbow, knee, expiration, breathing, and wrist pulses. This research provides a route to manufacture flexible sensors for next‐generation intelligent wearable devices. Abstract : A facile and effective surface micro‐dissolution method is developed to prepare carbon nanotubes (CNTs)‐coated PET fabric by embedding CNTs layers into a superficial polymer matrix. When fixed at a joint, the assembled sensor (CCPFS) can monitor joint movements in human fingers, wrist, elbow, knee, expiration, breathing, and wrist pulses.